2014
DOI: 10.1186/1476-4598-13-186
|View full text |Cite
|
Sign up to set email alerts
|

MiR-124 suppresses tumor growth and metastasis by targeting Foxq1 in nasopharyngeal carcinoma

Abstract: BackgroundThe molecular mechanisms underlying dysregulation of microRNAs have been documented in nasopharyngeal carcinoma (NPC). Our previous study demonstrated that plasma miR-124 was down-regulated in NPC using microarray analysis and quantitative PCR validation. Though growing studies showed that down-regulated miR-124 was closely related to tumourigenesis in various types of cancers, the role of miR-124 in NPC remains largely unknown.MethodsThe expression level of miR-124 was evaluated in NPC cell lines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(110 citation statements)
references
References 40 publications
8
100
0
1
Order By: Relevance
“…miR-124 suppressed tumor growth and metastasis by targeting FOXQ1 in nasopharyngeal cancer (50). An additional previous study suggested that there was a double-negative feedback loop between miR-422a and its targeted gene, FOXQ1, in HCC (51).…”
Section: Discussionmentioning
confidence: 99%
“…miR-124 suppressed tumor growth and metastasis by targeting FOXQ1 in nasopharyngeal cancer (50). An additional previous study suggested that there was a double-negative feedback loop between miR-422a and its targeted gene, FOXQ1, in HCC (51).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, miR-506 may be a promising miRNA for targeting FOXQ1. In addition, miR-124 is reportedly capable of targeting and inhibiting FOXQ1 to suppress tumor growth and metastasis in nasopharyngeal cancer (27). Zhang et al (26) reported that FOXQ1 is a target gene of miR-422a and that the overexpression of miR-422a inhibited the proliferation and migration of hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that FOXQ1 expression can be regulated by specific miRNAs in cancers (26,27). Bioinformatic research revealed that FOXQ1 has a putative binding site for miR-506 (Fig.…”
Section: Foxq1 Is a Potential Target Of Mir-506mentioning
confidence: 99%
“…Эпигенетическое выключение 3 локусов miR-124 (miR-124-1 / 2 / 3) наблюдается не только в опухолях головного мозга, но и при раз-личных других типах рака, таких как рак толстой киш-ки (75 % случаев), молочной железы (32-50 %), легких (48 %), лейкозе (36 %) и лимфоме (41 %). В контексте ОГШ рядом авторов был описан антипролифератив-ный эффект miR-124 [66,67], что указывает на возмож-ность аналогичного феномена угнетения синтеза этой молекулы в процессе развития плоскоклеточного рака.…”
Section: Introductionunclassified